Relations of second throw time and the steal check rate of the baseball catcher using video recordings - Suzuki, C.; Fujii, M.; Murakami, K.; Nakamoto, H.; Maeda, A. (Japan Journal of Physical Education, Health and Sport Sciences, 2019)
One of the important roles of a baseball catcher is to check whether an opponent is trying to steal a base. This checking action must occur as part of other events: a quick throwing action (short operation time), a high ball speed (short duration of ball flight), and accurate tagging (the time from the fielder catching the ball to touching the opponent runner is short). In other words, in order for the catcher to check whether an opponent is trying to steal a base, it is necessary to shorten the time between catching the ball and when the fielder touches the opponent runner. However, the relationship between the time and the possibility of checking for an attempt to steal a base and the influence of each phase on the steal check rate have not been examined. The present study investigated the relationship between the time required to prevent a steal and the steal check rate of a baseball catcher using video recordings. The video recordings used for our analysis were videos of steal check successes and failures in exhibition and official university and amateur baseball games, with a focus on runners attempting to steal second base. We classified Motion Time as the period from catching the initial pitch to ball release, Ball Time as the period from ball release to ball arrival at second base, and Touch Time as the period from ball arrival at second base to the fielder touching the runner; the sum of these 3 phases was defined as All Time, and the sum of Motion Time and Ball Time was defined as Pop Time. We constructed 3 models in which the success or failure of the steal check was set as a target variable and each phase time as an explanatory variable, and performed logistic regression analysis on each model. As a result, we clarified that the baseball catcher could check for a steal if the All Time was less than 2.429 s, and there was a significant negative correlation between the steal check rate and All Time. In addition, among the three phases, Touch Time had the greatest effect on the steal check rate. Therefore, it was suggested that accurate throwing is the most important factor in preventing a steal to second base.